Candiates for delegate to the Democratic Party National Convention
This document lists candidates for delegate to the Democratic Party National Convention, grouped by presidential preference. It identifies delegates pledged to Eugene J. McCarthy, delegates pledged to Robert F. Kennedy, and a group expressing no preference, chaired by Thomas C. Lynch. Each section provides extensive name listings, including public officials, community leaders, and prominent figures from California. The format organizes delegates by preference slate, reflecting the internal alignment within the state delegation during the 1968 nomination contest. Overall, the document serves as a comprehensive roster of delegate candidates and their declared presidential loyalties.